Parent involvement and students’ academic performances in high schools in Kalay, Myanmar - Piang, Van Khua; Leksansern, Arisara (Kasetsart Journal of Social Sciences, 2021)
This research investigated the relationships between six types of parent involvement suggested by Epstein comprising type 1 parenting, type 2 learning at home, type 3 communicating, type 4 volunteering, type 5 decision making and type 6 collaborating, and students’ academic performances comprising engagement, achievement in term of grade, attendance and attitude toward school in high schools, Kalay, Myanmar. Data were collected using questionnaires from 350 pairs of parents and students (350 grade 10 students and 350 parents), recruited using proportion and simple random sampling methods. Data were analyzed using basic statistics and Person Correlation analysis. Analysis showed that type 1 parenting, type 2 learning at home, and type 4 volunteering were significantly correlated with students’ performances, particularly with engagement and achievement in terms of grade. Type 3 communicating was also positively associated with student achievement in terms of grade, while type 4 volunteering performed by male and female parents differently affected attendance. Type 4 Volunteering performed by parents with a high school and below education level was negatively associated with student’s attitude toward school. The findings presented critical evidence to confirm parent involvement was crucial in education. The study suggested the policy makers and the local education authorities consider the results of this study to develop and implement strategies to enhance parent involvement, and that parents continuously express their expectation, care and love to their children as well as focusing on building a good relationship with their children through parenting and learning at home activities.